Microbacterium oxydans and preparation method and application of film coating agent of microbacterium oxydans

By using the composite coating agent prepared by Microbacterium oxydans, the plant endogenous ethylene was degraded, which solved the problem of Lanzhou lilies prone to aging, discoloration and rot during storage, and achieved the effect of significantly extending the shelf life and improving commercial properties.

CN119752685APending Publication Date: 2025-04-04GANSU UNIV OF CHINESE MEDICINE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411756346.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

During the mining and storage process, Lanzhou lilies are prone to accelerate breathing and increase ethylene generation, which in turn causes bulbs to aging, discoloration and rot, affecting food safety and industrial development.

Method used

Microbacterium oxydans (named MV-PHGII-2) were used to prepare coating agents that degrade plant endogenous ethylene. The strain was bound to sodium alginate and zein through embedding technology to form a composite coating agent. The coating agent is soaked on the Lanzhou lily bulb sheet, formed a film in CaCl2 solution, and finally stored at low temperature.

Benefits of technology

It significantly reduces the browning of the lily bulbs in Lanzhou, slows down the respiration rate and MDA content, inhibits the activity of POD and PAL enzymes, delays the aging process, and shows better storage effects at low temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses microbacterium oxydans and application thereof in preparation of a preparation for degrading plant endogenous ethylene, and further discloses a preparation method, application and application mode of a microbacterium oxydans film coating agent. The method for preparing the film coating agent comprises the following steps: preparing a zein solution, preparing a sodium alginate solution and preparing the film coating agent. The M.oxydans MV-PHGII-2 which is good in safety and relatively high in ACCD enzyme activity is separated and screened out, and the composite coating agent is prepared by using an embedding technology; and a plurality of index test results are integrated, so that the aging process of the Lanzhou lilies can be delayed and the quality of the picked Lanzhou lilies can be kept stable by compounding the low-temperature material and the color polishing material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biological preservation, and in particular relates to a preparation method and application of a Microbacterium oxidans and a coating agent thereof. Background Art

[0002] Lanzhou lily Lilium davidii var. willmottiae (EH Wilson) Raffill is a variety of Lilium spp., a perennial herb. Lanzhou lily is a famous and high-quality vegetable with medicinal and edible properties. Its bulb epidermis is fragile, has a high water content and is rich in nutrients. During the harvesting and storage process, it is easy to cause accelerated respiration and increased ethylene production, which in turn causes problems such as bulb aging, discoloration and decay, which has a serious impact on food safety and hinders the healthy development of the Lanzhou lily industry. Therefore, finding a natural, efficient, environmentally friendly and economical post-harvest storage and preservation method is of great significance to prolong the shelf life of Lanzhou lily and improve its commercial quality.

[0003] 1-aminocyclopropane-1-carboxylic acid (ACC) is a precursor for the synthesis of endogenous ethylene in plants. When plants are subjected to environmental stimuli, they will synthesize a large amount of ethylene, which will promote plant aging and decay. Studies have shown that some rhizosphere bacteria in the soil can synthesize 1-aminocyclopropane-1-carboxylic acid deaminase (ACCD), which decomposes the precursor of ethylene ACC into ammonia and α-ketobutyric acid, thereby reducing the level of ethylene in plants and delaying plant aging. ALI et al. used Pseudomonas fluorescens YsS6 to delay the aging of carnation cut flowers. However, since environmental conditions have a great influence on strains and enzymes, various dosage forms are usually prepared by encapsulation technology to improve chemical stability and expand the scope of application. Zhao Qun et al. used sodium alginate / polyvinyl alcohol composite to fix acetic acid bacteria, which enhanced the acid production and acid production stability of acetic acid bacteria. Wu Yue et al. used arabinoxylan and sodium alginate composite to encapsulate plant lactobacillus, which effectively improved the storage stability of lactobacillus. However, there are few studies on the encapsulation technology of ACCD active strains, especially in the field of fruit and vegetable preservation. Summary of the invention

[0004] One of the objects of the present invention is to provide a Microbacterium oxidans; The second object of the present invention is to provide the use of Microbacterium oxidans in the preparation of a preparation for degrading endogenous ethylene in plants; The third object of the present invention is to provide a method for preparing a Microbacterium oxidans coating agent; The fourth object of the present invention is to provide an application of the Microbacterium oxidans coating agent; A fifth object of the present invention is to provide an application method of the Microbacterium oxidans coating agent.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is: A Microbacterium oxidans, the Microbacterium oxidans Microbacterium oxydans , named MV-PHGII-2, was deposited in the General Microbiology Center of China Microorganism Culture Collection Administration on November 18, 2024, with the deposit number CGMCC NO. 32549, and the sequence is shown in SEQ ID No.1.

[0006] The invention discloses an application of Microbacterium oxidans in preparing a preparation for degrading endogenous ethylene in plants.

[0007] A method for preparing a coating agent using Microbacterium oxidans comprises the following steps: S1. Preparation of zein solution: Take 0.3 g of zein and dissolve it in 5 ml of 60% ethanol solution; S2. Preparation of sodium alginate solution: Dissolve sodium alginate in 15 ml water at 80 °C according to the concentration; S3. Preparation of coating agent: After mixing the zein solution and the sodium alginate solution with a concentration of 2%-6%, glycerol was added and magnetic stirring was carried out at 600 r / min for 10 min to obtain a carrier solution. The carrier solution was sterilized at 120 °C and cooled, and then added to OD 600 The bacterial solution was 0.8, and then dropped into CaCl2 solution for fixation for 5 minutes to prepare the coating agent.

[0008] In order to further realize the present invention, the amount of glycerol added in S3 is 10%-30% of the total amount of the zein solution, the sodium alginate solution and the bacterial solution.

[0009] In order to further realize the present invention, the concentration of the CaCl2 solution in S3 is 1%-5%.

[0010] In order to further realize the present invention, the concentration of the sodium alginate solution in S3 is 3.4%.

[0011] In order to further realize the present invention, the added amount of glycerol is 22.8% of the total amount of the zein solution, the sodium alginate solution and the bacterial solution.

[0012] In order to further realize the present invention, the concentration of the CaCl2 solution is 2.8%.

[0013] Application of a coating agent prepared by Microbacterium oxidans in the preservation of Lanzhou lily.

[0014] In order to further realize the present invention, the method of using the oxidizing Microbacterium to prepare the coating agent in the preservation of Lanzhou lily is to soak the bulb pieces of Lanzhou lily in the coating agent for 3 minutes, soak them in a 2.8% CaCl2 solution for 5 minutes to form a film, take them out, wait for natural drying, and store them at a relative humidity of 55% and a temperature of 4°C.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention separates and screens the ACCD enzyme with good safety and high activity. M. oxydans MV-PHGII-2 was used to prepare a composite coating agent using encapsulation technology.

[0016] The present invention uses sodium alginate (SA) and zein as substrates to embed the isolated and screened safe strains with high ACCD activity, prepares a composite coating agent and optimizes the process. The optimal process conditions of the coating agent obtained after process optimization are: SA concentration 3.4%, glycerol (Gl) addition amount 22.8%, CaCl2 concentration 2.8%. Under this process condition, the embedding rate of the strain is 60.56%, which effectively improves the chemical stability of the strain and its ACCD. Through the study of the structure and performance of the coating agent, it is found that the coating agent presents a typical honeycomb network structure, and the components generate interaction forces, and the structural stability is good. Subsequently, the prepared coating agent is used to preserve Lanzhou lily at different temperatures. The results show that compared with the uncoated group, the coating treatment can significantly reduce the browning degree of Lanzhou lily bulb slices, slow down the respiration rate and MDA content, and inhibit the activity of POD and PAL enzymes, thereby delaying its aging process. And under the same treatment conditions at 4℃, it has a better storage effect.

[0017] The present invention characterizes the morphology and characteristics of the film by SEM, FT-IR, XRD and other methods and evaluates its preservation effect on Lanzhou lily at different temperatures, in order to provide a scientific basis for studying new technologies for Lanzhou lily preservation. Comprehensive test results of multiple indicators show that the combination of low temperature and polishing materials can also delay the aging process of Lanzhou lily and maintain stable quality after picking. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The results of qualitative screening of ACCD active strains in the present invention, wherein a is the screening result of DF medium, and b is the screening result of ADF medium; Figure 2 The hemolytic test results of each strain in the present invention are shown in FIG. Figure 3The single factor effects on the embedding rate and ACCD activity of the strain in the present invention, wherein a is the effect of SA concentration, b is the effect of Gl addition, and c is the effect of CaCl2 concentration; Figure 4 The influence of various factors on the embedding rate of the strain in the present invention; Figure 5 The microscopic morphology of SA, Zein and coating agent in the present invention, wherein a is SA, b is Zein, c is the surface and cross section of the coating agent, and d is the cross section of the coating agent; Figure 6 is the FTIR spectrum of the coating agent in the present invention; Figure 7 is the XRD spectrum of the coating agent in the present invention; Figure 8 The effect of the coating agent of the present invention on the appearance quality of Lanzhou lily; Fig. 9 The effect of the coating agent of the present invention on the browning degree of Lanzhou lily; Fig.10 The effect of the coating agent of the present invention on the respiration rate of Lilium lanzhouense; Fig.11 The effect of the coating agent of the present invention on the PAL activity of Lilium lanzhouense; Fig.12 The effect of the coating agent of the present invention on the POD activity of Lilium lanzhouense; Fig.13 This is the effect of the coating agent in the present invention on the MDA content of Lilium lanzhouense. DETAILED DESCRIPTION

[0019] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0020] A Microbacterium oxidans, the Microbacterium oxidans Microbacterium oxydans , named MV-PHGII-2, was deposited in the General Microbiology Center of China Microorganism Culture Collection Administration on November 18, 2024, with the deposit number CGMCC NO. 32549, and the sequence is shown in SEQ ID No.1.

[0021] The invention discloses an application of Microbacterium oxidans in preparing a preparation for degrading endogenous ethylene in plants.

[0022] A method for preparing a coating agent using Microbacterium oxidans comprises the following steps: S1. Preparation of zein solution: Take 0.3 g of zein and dissolve it in 5 ml of 60% ethanol solution; S2. Preparation of sodium alginate solution: Dissolve sodium alginate in 15 ml water at 80 °C according to the concentration; S3. Preparation of coating agent: After mixing the zein solution and the sodium alginate solution with a concentration of 2%-6%, glycerol was added. The amount of glycerol added was 10%-30% of the total amount of the zein solution, the sodium alginate solution and the bacterial solution. The carrier solution was obtained by magnetic stirring at 600 r / min for 10 min. The carrier solution was sterilized at 120 °C and cooled, and then added to OD 600 The bacterial liquid is 0.8, and then dripped into CaCl2 solution for fixation for 5 minutes. The concentration of CaCl2 solution is 1%-5%, and the coating agent is prepared.

[0023] Among them, the optimal concentration of sodium alginate solution is 3.4%.

[0024] Among them, the optimal addition amount of glycerol is 22.8% of the total amount of zein solution, sodium alginate solution and bacterial solution.

[0025] Among them, the optimal concentration of CaCl2 solution is 2.8%.

[0026] Application of a coating agent prepared by Microbacterium oxidans in the preservation of Lanzhou lily.

[0027] The method of using the coating agent prepared by Microbacterium oxidans in the preservation of Lanzhou lily is to soak the bulb pieces of Lanzhou lily in the coating agent for 3 minutes, then soak them in a 2.8% CaCl2 solution for 5 minutes to form a film, take them out, wait for natural drying, and store them at a relative humidity of 55% and a temperature of 4°C.

[0028] Experimental Example 1: Screening of ACCD active strains, structural observation, activity and safety determination: 1. Materials and reagents: Lilium lanzhouense was provided by Lanzhou Tiantian Lily Co., Ltd. in Xiguoyuan Town, Qilihe District, Lanzhou City. The experimental strains (Table 1) were all from the rhizosphere soil of Lilium lanzhouense and stored in this laboratory.

[0029] Sodium alginate (SA), zein (Zein) and glycerol (Gl) were all analytically pure; α-ketobutyric acid, 2,4-dinitrophenylhydrazine and calcium chloride (CaCl2) were all analytically pure; DF, ADF and TSB culture media; Columbia blood agar plates.

[0030] 2. Screening of ACCD-active strains Referring to the method of PENROSE et al., the strain was inoculated into DF and ADF medium respectively and cultured at 28 °C for 3-5 d. After three subcultures, if the strain can grow on ADF medium, it means that the strain can degrade ACC, that is, the strain can synthesize ACCD.

[0031] Figure 1 It was observed that each strain could grow on ADF medium after three consecutive subcultures, indicating that all eight strains could synthesize ACCD. Among them, the growth effect of Y6 strain in ADF medium was better than that in DF medium, which preliminarily showed that Y6 strain had a higher ability to synthesize ACCD.

[0032] 3. Strain morphology and activity determination The cells were streaked on TSB plate medium and cultured at 28 °C for 24 h, and the colony morphology was recorded.

[0033] ACCD activity was determined by the method of Li Mingyuan et al. with some improvements. The cells were washed with DF solution and then resuspended in ADF solution for 24 h. The bacterial solution was centrifuged for 10 min, the supernatant was discarded, and the cell mass was collected and determined. The 2,4-dinitrophenylhydrazine colorimetric method was used for determination. ACCD activity is expressed in μmol / (mg·h), which is the amount of α-ketobutyric acid produced by 1 mg of enzyme protein within 1 h.

[0034] From Table 2, it can be found that the colonies of these strains are mostly round and white, some colonies have moist and smooth surfaces, while others are relatively dry. Quantitative analysis found that Y6 had the highest enzyme activity among all strains, reaching 0.119±0.006μmol / (mg·h), while Y7 had the lowest enzyme activity. Compared with Y7, the enzyme activity of Y6 was about 4.41 times that of Y7.

[0035] 4. Determination of hemolytic activity of strains Take 5 μl of bacterial solution and inoculate it on a blood red plate. Set three replicates on each plate at equal intervals. Incubate at 28°C for 24 h and observe whether there is a transparent hemolytic zone around the colony.

[0036] Figure 2 It was observed that there were obvious hemolytic transparent circles around the colonies of Y1, Y3, Y4 and Y8, indicating that they had hemolytic effects; while the colonies of the other strains did not have such circles, indicating that these strains did not have hemolytic ability and had good safety. Therefore, after comprehensive consideration, Y6 was used for subsequent film preparation tests.

[0037] Experimental Example 2: Determination of embedding rate, optimization of preparation process and structural analysis of coating agent: 1. Determination of coating agent embedding rate Take 1 g of the coating agent and put it into a sterile test tube. Add 2 ml of 0.2 M sodium bicarbonate and 8 ml of 0.06 M trisodium citrate solution. After disintegration in an oscillator at 28°C and 180 r / min, take 1 mL of the sample and dilute and spread it on a plate, and calculate the embedding rate of the strain in the coating agent.

[0038] The formula for calculating the embedding rate is: Y (%) = (amount of bacteria embedded in the coating agent / total amount of bacteria) × 100 2. Effect of single factor on strain embedding rate and ACCD activity Referring to Ling Xiaodong et al., three single factors, SA concentration, Gl addition and CaCl2 solution, were investigated to analyze the influence of each factor on the strain embedding rate and ACCD activity of the coating agent. The conditions were SA concentration: 2%, 4%, 6%, 8%; Gl addition: 10%, 20%, 30%, 40%; CaCl2 concentration: 0%, 1%, 3%, 5%.

[0039] according to Figure 3 It can be seen that SA concentration, Gl addition and CaCl2 concentration all have an effect on the embedding rate of strains and ACCD activity. The possible reason is that increasing SA concentration is conducive to the electrostatic interaction between SA and Zein to form a dense network structure, but when SA is high, the structure is too tight, which makes the magnetic stirring effect worse, thereby affecting the embedding efficiency. Secondly, glycerol can enhance the hydrogen bonding between protein molecules and improve the embedding efficiency. However, excessive glycerol has strong water absorption, which weakens the intermolecular interaction force, increases the porosity between polymer molecules, and leads to a large amount of embedding material loss, thereby reducing the embedding effect. CaCl2 is a commonly used cross-linking agent that can form a stable three-dimensional structure with SA. As the CaCl2 concentration increases, the cross-linking degree becomes stronger, but a higher CaCl2 concentration will reduce the permeability of the membrane, resulting in a poor embedding effect.

[0040] 3. Optimization of coating agent preparation process Based on the results of the single factor test, the main factors SA concentration (X1), Gl addition (X2) and CaCl2 concentration (X3) were optimized by response surface method with embedding rate (Y) as the response value. The design of factors and levels is shown in Table 3, and the regression model analysis was performed using Design-Expert software.

[0041] According to the above test results, the regression equation of the independent variable and embedding rate (Y) is: = 58.19-6.01 A +9.89 B -6.03 C -3.58 AB -6.01 AC-0.32 BC -10.1 A 2 -20.33 B 2 -18.55 C 2 As can be seen from Table 5, the model P Value = 0.0001<0.01, the difference is extremely significant, and the lack of fit item is 0.2509 ( P >0.05), not significant, R 2 and R 2 Adj The values ​​of the model and experimental data are 0.9752 and 0.9433 respectively, which indicates that the model fits the experimental data well. The confidence of the regression equation of the model is high and the error is small, so it can be used to predict the embedding rate of strains.

[0042] from Figure 4 It can be seen that the interaction between SA concentration and CaCl2 concentration is strong, while the interaction between Gl addition amount and CaCl2 concentration is weak; Gl addition amount has a higher degree of influence on the embedding rate than SA concentration and CaCl2 concentration, and the effect of SA concentration on the embedding rate is better than CaCl2 concentration, indicating that Gl addition amount and SA concentration are the main factors affecting the coating agent.

[0043] The predicted value of the embedding rate of the strain recommended by Design-Expert 13 is 60.81%. Considering the operability in practical application, the optimal process was corrected by the response surface: SA concentration 3.4%, Gl addition 22.8%, CaCl2 concentration 2.8%. After three repeated tests, the average value of Y was 60.56%. Compared with the predicted value, the deviation is small, and the model is reliable.

[0044] 4. Structural analysis of coating agents 4.1 SEM measurement The ultrastructures of SA, Zein, and coating agents were observed using a scanning electron microscope (10 kV).

[0045] Depend on Figure 5 A and Figure 5 As shown in Figure b, SA and Zein are irregular particles and dispersed evenly. However, after the two are made into coating agents, their SEM morphology changes significantly and a heterogeneous structure appears. Figure 5As shown in Figure c, the surface of the membrane is dense and compact with folds and creases, which may be due to the dehydration shrinkage effect of the membrane surface structure during the curing process, while the cross section of the membrane is loose and porous. Further observation of the cross section at 2.00 kx revealed that the interior presents a typical honeycomb network structure. This structure provides sufficient space for the coating agent to store bioactive ingredients and has a better protective effect on the encapsulated ingredients.

[0046] 4.2 Infrared spectroscopy (FT-IR) analysis The chemical structure changes of SA, Zein and coating agent were analyzed by FT-IR with a scanning range of 4000 cm -1 -400 cm -1 , resolution 2 cm -1 .

[0047] Figure 6 FT-IR spectra of SA, Zein and coating agent. Compared with SA and Zein, the OH characteristic absorption peak of the coating agent becomes broader and blue-shifted, and the hydrogen bonds increase; 1629 cm -1 The characteristic peak of Zein's amide I band, the corresponding peak in the coating agent migrated to 1645 cm -1 , indicating that there may be a hydrophobic effect in the binding process between Zein and SA; 1417 cm -1 The peak at is the COO-stretching vibration absorption peak of SA, and in the coating agent, the peak is red-shifted, indicating that SA has been successfully wrapped on Zein. In summary, there is a good correlation between the characteristic absorption peak of the infrared spectrum and the composition change of the coating agent, which enhances the stability and network density of the coating agent.

[0048] 4.3 X-ray diffraction (XRD) analysis SA, Zein and coating agent were analyzed by XRD. The test conditions were: cuka (40 kV, 40 mA) as the radiation source, 5°-60° as the scanning angle (2θ), and about 2° / min as the scanning speed.

[0049] Figure 7 The XRD spectra of SA, Zein and coating agent are shown in Figure 1. In the figure, the weak peaks and sharp peaks of SA and Zein appear at 13.49°, 9.12°, 20.37° and 19.8° respectively. After the two substrates are prepared into coating agents, the weak peaks of SA and Zein gradually disappear and a broad peak appears at around 21.94°, indicating that the two substrates can be compatible to a certain extent and produce hydrogen bonds, thereby making the film structure more stable.

[0050] Experimental Example 3: Application of coating agent in the preservation of Lanzhou lily: 1. Sample processing Lanzhou lily bulb pieces of similar size were soaked in 5% sodium hypochlorite for 10 min, washed with sterile water and dried, and then randomly divided into three groups.

[0051] (1) Control group (CK): The bulb slices were soaked in sterile water for 8 min, represented by T1.

[0052] (2) Immerse the bulb slices in the bacterial solution for 8 min, represented by T2.

[0053] (3) Soak the bulb slices in the film solution for 3 min, and then soak them in 2.8% CaCl2 solution for 5 min to form a film, which is represented by T3. Each test was repeated 3 times.

[0054] After the above three treatments were dried naturally, they were stored at a relative humidity of 55% for 15 days. Two treatments, low temperature (4°C) and room temperature (20°C), were set up, and the relevant indicators were measured every 3 days.

[0055] 2. Effects of coating agents on appearance quality, browning degree and respiration rate of Lanzhou lily The browning degree was determined by colorimetry, and the respiration rate was determined by static method.

[0056] Depend on Figure 8 It can be seen that with the extension of storage period, the color of the bulb pieces of Lanzhou lily at low temperature and room temperature will gradually change from bright and clean white to brown to purple-red. The bulb pieces of T1 group all began to turn brown on the 3rd day, the bulb pieces of T2 group began to turn brown on the 6th and 9th days respectively, and the bulb pieces of T3 group only showed slight browning on the 12th day.

[0057] Depend on Fig. 9 It can be seen that the browning degree of the two groups of Lanzhou lilies showed an upward trend. The browning degree of the T1 group at room temperature increased the fastest, reaching 9.13±0.2 at 15 days, which was 2.12 times that of the T3 group. After 15 days of storage at low temperature, the browning degree of the T3 group was 3.82±0.05, which was 0.89 times that of the T3 group at room temperature. The results showed that the coating treatment could effectively delay the browning process of the Lanzhou lily bulb slices, inhibit the browning degree of the lily, and showed a better inhibitory effect at room temperature.

[0058] Depend on Fig.10It can be seen that the respiratory intensity of the T3 group was significantly lower than that of the CK during the entire storage period (P<0.05). At room temperature, the T1 and T2 groups had a respiratory peak on the 12th day, with peak values ​​of 107.59 mg / (kg•h) and 68.03 mg / (kg•h), respectively; while at low temperature, only the T1 group had a respiratory peak of 72.82 mg / (kg•h). The possible reason is that the density of the coating agent reduces the oxygen permeability to inhibit the metabolic rate of the lily, creating a low oxygen and high carbon dioxide environment to inhibit the metabolic rate of the Lanzhou lily; on the other hand, it may be that ACC has been degraded, the ethylene production has decreased, and the respiratory rate of the Lanzhou lily has been inhibited. This shows that the coating treatment can delay the senescence of the Lanzhou lily, reduce its respiration and postpone the occurrence of the respiratory peak.

[0059] 3. Effects of coating agents on MDA content and related enzyme activities in Lilium lanzhouensis MDA content, POD and PAL kits (purchased from Beijing Box Biotechnology Co., Ltd.) were used for determination, and the operating steps are detailed in the corresponding instructions.

[0060] like Fig.11 The results showed that the PAL activity of lily increased and then decreased during storage. Ethylene induced PAL synthesis, thereby increasing PAL activity. As time went on, PAL activity gradually weakened because it could be regulated by feedback inhibition of its products. After 15 days of storage, the PAL activities of the T1, T2 and T3 groups under low temperature were 3.65±0.33 U / g, 3.14±0.13 U / g and 2.53±0.15 U / g, respectively, which were 0.77 times, 0.98 times and 0.96 times that of the normal temperature group, respectively, indicating that the combined use of low temperature and coating agent can inhibit the PAL activity and accumulation of phenolic substances in lily bulb slices and slow down their senescence.

[0061] Fig.12 The results showed that the activity of POD in groups T1 and T2 increased first and then decreased, while the activity of POD in group T3 increased slowly and was lower than that in groups T1 and T2 (P < 0.05), indicating that the coating treatment could inhibit the increase of POD in lily and reduce its browning. During the cold storage period, the activity of POD in groups T1, T2 and T3 all showed an increasing trend. At 15 days, they reached 197.0 ± 14.36 U / g, 159.23 ± 9.11 U / g and 97.15 ± 7.21 U / g, respectively. Among them, the higher activity of POD in group T1 indicated that the cell damage in group T1 during the cold storage period was aggravated, which was consistent with the browning law of group T1 under low temperature mentioned above. In summary, the coating treatment can reduce the activity of POD in lily and inhibit the browning of Lanzhou lily.

[0062] Depend on Fig.13The results showed that the MDA content of each treatment group increased during the storage period. After 15 days of storage, the MDA content of groups T1 and T2 was significantly higher than that of group T3 (P<0.05). Compared with the initial content, the growth rates of groups T1, T2 and T3 under low temperature were 163.83%, 155.81% and 85.05%, respectively, which were lower than the growth rates at normal temperature. This indicates that low temperature and coating treatment can slow down the damage of cell membrane of Lanzhou lily during storage and inhibit its senescence.

Claims

1. A Microbacterium oxidans, characterized in that: Microbacterium oxydans Microbacterium oxydans , named MV-PHGII-2, was deposited in the General Microbiology Center of China Microorganism Culture Collection Administration on November 18, 2024, with the deposit number CGMCC NO.32549, and the sequence is shown in SEQ ID No.

1.

2. Use of the Microbacterium oxidans as claimed in claim 1 in the preparation of a preparation for degrading endogenous ethylene in plants.

3. A method for preparing a coating agent using the Microbacterium oxidans described in claim 1, characterized in that The steps include: S1. Preparation of zein solution: Take 0.3 g of zein and dissolve it in 5 ml of 60% ethanol solution; S2. Preparation of sodium alginate solution: Dissolve sodium alginate in 15 ml water at 80 °C according to the concentration; S3. Preparation of coating agent: After mixing the zein solution and the sodium alginate solution with a concentration of 2%-6%, glycerol was added and magnetic stirring was carried out at 600r / min for 10 min to obtain a carrier solution. The carrier solution was sterilized and cooled at 120°C and then added to OD 600 The bacterial solution was diluted to 0.8, and then dropped into CaCl2 solution for fixation for 5 minutes to obtain a coating agent.

4. The method for preparing a film coating agent as claimed in claim 3, characterized in that: The amount of glycerol added in S3 is 10%-30% of the total amount of the zein solution, the sodium alginate solution and the bacterial solution.

5. The method for preparing a film coating agent as claimed in claim 3, characterized in that: The concentration of the CaCl2 solution in S3 is 1%-5%.

6. The method for preparing a film coating agent as claimed in claim 3, characterized in that: The concentration of the sodium alginate solution in S3 is 3.4%.

7. The method for preparing a film coating agent as claimed in claim 4, characterized in that: The added amount of glycerol is 22.8% of the total amount of the zein solution, the sodium alginate solution and the bacterial solution.

8. The method for preparing a film coating agent as claimed in claim 5, characterized in that: The concentration of the CaCl2 solution is 2.8%.

9. Use of a coating agent prepared by the method as claimed in any one of claims 3 to 8 in preserving Lanzhou lilies.

10. The use as claimed in claim 9, characterized in that: The application method is to soak the bulb pieces of Lanzhou lily in the coating agent for 3 minutes, then soak them in a CaCl2 solution with a concentration of 2.8% for 5 minutes to form a film, take them out, wait for natural drying, and store them at a relative humidity of 55% and a temperature of 4°C.

Citation Information

Patent Citations

  • Method for separating plant growth-promoting rhinoacteria on copper tailings and evaluating performances of plant growth-promoting rhinoacteria

    CN106867944A

  • Salt-tolerant potassium-solubilizing growth-promoting microbacterium oxydans 41-C8, microbial agent and application thereof

    CN113046263A